Production of high purity granular metals: cadmium, zinc, lead - Shcherban, O. P.; Kovtun, G. P.; Gorbenko, Yu. V.; Solopikhin, D. О.; Virich, V. D.; Pirozhenko, L. О. (Technology and design in electronic equipment, 2017)
Cadmium, zinc and lead are constituent components of many semiconductor compounds. The obtained high purity distillates and ingots are large-size elements, which is not always convenient to use, and thus require additional grinding, which does not always allow maintaining the purity of the original materials. For the growth of semiconductor and scintillation single crystals, it is advisable to use "friable" granular high-purity distillates, which can be processed without the risk of contamination. For example, the European low-background experiment LUCIFER required more than 20 kg of high-purity granulated zinc, which was agreed to be supplied by NSC KIPT. This task was then extended to cadmium and lead.Motivated by these tasks, the authors of this paper propose complex processes of deep refining of cadmium, zinc and lead by vacuum distillation. A device producing granules has been developed. The process of granulation of high-purity metals is explored.The purity of produced granules for cadmium and zinc is >99,9999 and >99,9995% for lead granules. To prevent oxidation of metal granules during exposition to air, chemical methods of surface passivation were used. Organic solvent based on dimethylformamide used as a coolant improves the resistance of granules to atmospheric corrosion during the granulation of high purity Cd, Zn and Pb.